KEMAMPUAN MEMBACA CEPAT DENGAN KEMAMPUAN BERBAHASA INDONESIA SISWA KELAS VII SMP NEGERI 2 RANAH PESISIR KABUPATEN PESISIR SELATAN - Riska Mayeni; Alexander Syam (STKIP Pesisir Selatan, 2020)
The aims of this research were firstly, to describe an analysis result of correlationbetween speed reading and students Indonesian language competency at the class VII SMPN2 Ranah Pesisir of South Pesisir Regency. Secondly, students ability in reading speeds at the class VII SMPN 2 Ranah Pesisir of South Pesisir Regency. The type of this research was qualitative by using a descriptive method. Population of this research was all students at the class VII SMPN 2 Ranah Pesisir of South Pesisir Regency totally 128 people. Technique of data collection was random sampling with total sample about 33 people. Technique of data analysis used percentage score by calculating students speed reading ability and finding the average score of their ability toward the speed reading and understanding Indonesian reading based on their average score of the reading comprehension achievement. To know the correlation of each variable was measured by using product moment. The result of this research showed that the ability of students in speed reading at SMPN 2 Ranah Pesisir of South Pesisir Regency was in lower category; however their understanding toward Indonesian reading was higher. The result of research showed that there was a significant correlation between speed reading ability and students comprehension toward Indonesian reading ability of students at SMP Negeri 2 Ranah Pesisir of South Pesisir Regency.